Exploring the Integration of Computational Thinking and Mathematical Modelling in STEM Education - Fitriani, Fifi; Triandafillidis, Triandafillos; Thao, Le Phuong (jurnal matematika, 2023)
Purpose of the study: The aim of this study is to explore the effectiveness of integrating Computational Thinking (CT) and Mathematical Modelling (MM) in STEM education to improve students’ understanding of mathematical concepts, problem-solving skills, and engagement in the learning process. Methodology: This study utilized a quasi-experimental method with pre-test and post-test design. The sample of this study consisted of 200 students, who were randomly selected from four high schools in the Jambi City and Muaro Jambi areas. Tools included a mathematics achievement test and a student engagement questionnaire. Data were analyzed using paired t-tests and independent t-tests with the aid of SPSS software. Main Findings: The integration of Computational Thinking and Mathematical Modelling significantly improved students' understanding of mathematical concepts, problem-solving skills, and engagement. The experimental group showed a notable increase in post-test scores and higher engagement levels compared to the control group. Novelty/Originality of this study: This study introduces a novel framework for integrating Computational Thinking and Mathematical Modelling in STEM education, highlighting its potential to enhance both cognitive and affective aspects of learning. It provides empirical evidence supporting the use of innovative approaches to advance mathematics education.